Trade, Education, Governance and Distance: Impact on Technology Diffusion and Productivity Growth in Asia and LAC - Maurice Schiff; Yanling Wang (Global Labor Organization (GLO), 2017)
This paper examines the impact of North-South trade, education, governance and North-South distance, on technology diffusion and total factor productivity (TFP) growth in the South, focusing on LAC and East Asia over the 32 years before the Great Recession (1976-2007). Findings are: i) TFP rises with education, trade, governance (ETG) and imports' R&D content, and falls with distance to the North; ii) an increase of LAC's ETG to East Asia's levels raises TFP by 165%, fully accounting for its TFP gap with East Asia; iii) the impact of the education gap equals the sum of the governance and openness gaps; and iv) South America's loss of TFP relative to Mexico associated with its greater distance to US-Canada (both Europe and Japan) is 9.3 (0) percent.
Keywords: F22; J61; 330; Trade; Governance; Education; Distance; Technology Diffusion; Productivity growth